LINGKUNGAN KOTA LAYAK ANAK (CHILD-FRIENDLY CITY) BERDASARKAN PERSEPSI ORANGTUA DI KOTA YOGYAKARTA - Dodi Widiyanto; R. Rijanta (Bumi Lestari Journal of Environment, 2012)
The research aims at identifying the concepts related to child-friendly city as perceived by parents in Yogyakarta municipality. A structured questionnaire is employed to collect the data on the ideal urban environment of a child-friendly city as perceived by the respondents. The respondents are widthdrawn from four spots of locations in the city used as child playgrounds, i.e: Sultan Palace Yard, Taman Pintar (Smart Garden), Gembira Loka Zoo and Open Space under the flyover of Lempuyangan Station. Concepts related to child-friendly city are explored and grouped through a factor analysis. From the process of factor analysis, four measures of ideal urban environment related to child-friendly city can be identified. They are policy, protection, environment and planning for children. The first three concepts are well suited with the Indonesian national policy on child-friendly city. Whereas the last concept, planning for children, needs special  attention as a part of the existing concept of policy, or it should be an independent concept that needs to be accomodated in planning norms, standards, procedures and manuals in an urban environment.